2010
DOI: 10.2298/hel1053025t
|View full text |Cite
|
Sign up to set email alerts
|

Screening wild sunflower species and F1 interspecific hybrids for resistance to broomrape

Abstract: Broomrape has become one of the most important threats to the cultivated sunflower. New sources of resistance genes are needed to maintain sunflower production. The objective of this research was to evaluate accessions of wild sunflower species and their F 1 interspecific hybrids with cultivated sunflower for resistance to race E. Plant material consisted of 6 accessions of perennial species and 14 F 1 accessions between perennial species and cultivated sunflower as well as 42 accessions of annual species. Cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Variant of Pachenkov's (1973) method used in the quarantine chamber for testing sunflower breeding material in the greenhouse. The broomrape attack was assessed by uprooting and careful observation of root system for broomrape nodules and stalks Terzić et al (2010). Evaluation of the broomrape attack of selected hybrids in greenhouse conditions (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variant of Pachenkov's (1973) method used in the quarantine chamber for testing sunflower breeding material in the greenhouse. The broomrape attack was assessed by uprooting and careful observation of root system for broomrape nodules and stalks Terzić et al (2010). Evaluation of the broomrape attack of selected hybrids in greenhouse conditions (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Pancenko's (1973) method are used in all major breeding centers around the word. At the Institute of Field and Vegetable Crops a modification of Pachenkov's method is applied, the quarantine chamber for testing sunflower breeding material in greenhouse was done in plastic buckets (Dozet et al,1999), plastic tubes (Maširević and Medić-Pap, 2009 ) and in pots Terzić et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, plants of this species are completely resistant to broomrape from Yeysk area of Krasnodar region, so are the samples of H. debilis and H. praecox (Table 1). In researches of Terzić et al (2010) it is shown that in Serbia these species show resistance to race E of O. cumana. That corresponds to our data as well.…”
Section: Resultsmentioning
confidence: 99%
“…Many researches from other countries had reported earlier on the resistance of some annual and perennial wild species of sunflower to different races of O. cumana (Ruso et al, 1996;Christov, 1996;Christov et al, 2009;Fernandez-Martinez et al, 2000;Terzić et al, 2010). It has been proved that the wild species of Helianthus are the main source of the genes that control the resistance to new virulent races of broomrape.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the narrow genetic basis of cultivated sunflower for finding genes for the known races of the parasite research on wild sunflower species has been performed (Dozet & Marinković 1998, Fernadez-Martinez et al 2004, Jan 2004, Terzić et al 2010.…”
Section: Introductionmentioning
confidence: 99%